Mochtar Riady [Indonesia, banker] - Riady, Mochtar (Institutional Knowledge at Singapore Management University, 2015)
Founder and Chairman of Lippo Group, Mochtar Riady gained the moniker "Magic Man of Banking" because of his ability to turn around and grow several of Indonesia's private banks, the most notable being Bank Central Asia (BCA). But his 15 years in BCA wasn't all smooth sailing. He speaks to DNA about his challenges in BCA, which saw him dealing with sensitive relationships with the Suharto government, as well as the firing of his own son for Forex speculation.